The Influence of Education, Financial Literacy, and Non-Muslim Community Preferences on Interest in Using Sharia Financial Services (Study The Community of South Lore District): Pengaruh Edukasi, Literasi Keuangan, Dan Preferensi Masyarakat Non-Muslim Terhadap Minat Menggunakan Layanan Keuangan Syariah (Studi Pada Masyarakat Kecamatan Lore Selatan) - Andini Ulviya; Abdul Jalil; Noor Riefma Hidayah (Perisai : Islamic Banking and Finance Journal, 2026)
This research endeavors to examine the impact of education, financial literacy, and the preferences of non-Muslim communities on the inclination to utilize Sharia financial services within the Lore Selatan District. The investigation adopts a quantitative methodology utilizing an explanatory survey design. The sample comprises 199 respondents selected via purposive sampling, and the data were subjected to analysis through multiple linear regression techniques. The findings reveal that education does not exert a positive and significant impact, as evidenced by a t-value of -1.468 < t-table 1.985 with a significance level of 0.14 > 0.05. Conversely, financial literacy demonstrates a positive and significant influence on the interest of non-Muslim communities, reflected by a t-value of 6.650 > t-table 1.985 and a significance level of 0.00 < 0.05. Collectively, all three variables exert a significant effect on the interest of non-Muslim communities in employing Sharia financial services. These findings suggest that an enhanced public comprehension of the principles and advantages associated with Sharia financial services correlates with an increased propensity to utilize them. The findings emphasize that financial literacy and community preferences play a crucial role in increasing interest in Sharia financial services. Therefore, these results are expected to assist Sharia financial institutions in designing educational programs and strategies to enhance financial literacy and expand their reach to the non-Muslim community more effectively.